Charting the Skies and Seas: A Comparative Study of Career Awareness in Aviation and Maritime Professions Among Primary School Learners - Makola, Zamandlovu Sizile; Ngonyama-Ndou, Thuli; Tabane, Ramodungoane (Research in Social Sciences and Technology- OpenED Network, 2025)
The aviation and maritime sectors are vital for global transport and economic growth, yet attracting youth to these fields is challenging. This comparative analysis investigates primary learners' views on aviation and maritime careers, emphasising motivations, barriers and educational needs. Utilising Social Cognitive Career Theory (SCCT) and Social Learning Theory of Career Decision-Making (SLTCDM), the research assesses how early exposure, outcome expectations and self-efficacy influence learners' interest in these industries. By focusing on primary school learners, a largely overlooked group in career development research, this study contributes novel insights into early-stage career perceptions. A qualitative thematic analysis was conducted using feedback from learners attending a career exhibition targeting aviation and maritime professions. Results indicate that both fields are viewed as exciting and lucrative; however, aviation careers are linked to academic challenges and high training costs, while maritime roles are perceived as physically demanding and associated with prolonged family absences. Key motivators identified include financial security, opportunities for global travel and diverse career options, whereas significant barriers entail issues related to work-life balance, limited career awareness and industry-specific challenges. The findings underscore the need for structured career exposure, experiential learning, and mentorship programmes to connect learners with non-traditional careers. Practical implications include integrating career education into curricula, fostering industry-school partnerships, promoting gender diversity, and leveraging technology for career guidance. Addressing these challenges through targeted interventions can effectively attract a diverse, skilled workforce to the aviation and maritime sectors.